Pencahayaan Alami dan Preferensi Pemilihan Tempat Duduk di Kafe: Studi Kasus Jiakopi ATAS - Salsabila Ditaputeri; Wendy Sunarya (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Natural lighting plays a significant role in human life, particularly in terms of energy efficiency, physical health, and mental well-being. In the context of architectural design, natural lighting helps create warm, cheerful, and comfortable spaces, enhances aesthetics, and encourages people to stay longer. In cafés, natural lighting is essential for establishing a pleasant atmosphere that supports both social interaction and productivity. This study employs a qualitative approach and behavioral mapping to examine the influence of natural lighting on seating preferences among café visitors in Indonesia, with a specific focus on Jiakopi ATAS Café in Surabaya. This café, frequently visited by young people and professionals, is known for its modern, eco-friendly design that maximizes the use of natural light. The study investigates how natural lighting at Jiakopi ATAS affects visitors’ seating choices. The findings are expected to provide valuable insights for building and café owners or designers in creating environments that are not only aesthetically pleasing but also support the comfort and productivity of their users.